In search of the missing hand of 'collaborative action': evidence from the Indian medical device industry. Issue 1 (2nd January 2019) - Kale, Dinar; Wield, David
ABSTRACT: Some emerging countries have made significant progress in developing local pharmaceutical and biotechnology but had less success in building medical device industries (MDIs). This paper explores the weak development of local MDIs by analysing the contrasting evolutionary trajectories of Indian healthcare technology sectors. The Indian pharmaceutical and biotechnological industries have emerged as leading global suppliers of generic drugs and vaccines, in marked contrast to the medical devices industry. This paper reveals that existence of a weak collaborative linkage between medical device manufacturers and the Indian health system, which largely lacks a systemic and cross-sectoral linkages, and weak communication between industry and government policy-makers have become a huge barrier to the development of the Indian MDI in the contemporary neo-liberal environment. The weak connection between technology and industrial policy and healthcare policy objectives has severely hampered both development of national technological capabilities and the creation of affordable health care.